Sequence polymorphism of arabinogalactan and beta tubulin gene in kelampayan (Neolamarckia cadamba) - Tang, Leh Ee (Universiti Malaysia Sarawak (UNIMAS), 2011)
Neolamarckia cadamba or locally known as Kelampayan is an evergreen and tropical tree native to South Asia under the family of Rubiaceae. Kelampayan is the best raw material for plywood industry and also used as raw materials for pulp and paper industry. Arabinogalactan Proteins (AGPs) are extracellular proteoglycans that are implicated in plant growth and development. Tubulin is a major cytoskeleton protein and as a building block of microtubules. The cytoskeleton is important in plant cell shapes, cell division and cell transport. The main objective of this study was to identify the single nucleotide variation in the AGP and beta-tubulin gene of kelampayan. Genomic DNA was firstly extracted from six N. cadamba trees. Targeted DNA sequence of arabinogalactan (AGP) gene and beta tubulin (β-TUB) were amplified by Polymerase Chain Reaction (PCR) by using primer set. The 340 bp of AGP and 491 bp of β-TUB amplicons were subjected to BLASTn analysis to carry out the sequence homology search in the NCBI. Sequence alignment then was carried out by using ClustalW software for single nucleotide polymorphism (SNP) detection. One sequence variation within arabinogalactan gene which was caused by single nucleotide substitution was detected. Five sequence variations and one InDel polymorphism within beta tubulin were detected. The finding of SNPs in AGP and β-TUB was very important as a valuable marker in molecular selective breeding.